PEMELIHARAAN HUBUNGAN JARAK JAUH ANTARA ANAK DAN ORANG TUA YANG BEKERJA SEBAGAI TENAGA KERJA INDONESIA (TKI) DI LUAR NEGERI - Apriliansyah, Dimas; Naryoso, Agus; Qurrota Ayun, Primada (Interaksi Online, 2024)
Data from the Indonesian Migrant Worker Protection Agency (BP2MI) shows that throughout 2022, a total of 200,761 individuals were sent abroad to work as Indonesian Migrant Workers (PMI), also commonly known as Indonesian Workers (TKI). For TKI who already have families, they are required to engage in long-distance communication with the family members left behind, particularly with children and parents who experience these long-distance relationships. This research employs a qualitative approach with a descriptive method to describe the maintenance of long-distance relationships conducted by children and parents who work as TKI abroad. The research uses Communication Privacy Management Theory, Maintenance Relationship Theory, and Relational Dialectics Theory. Data collection techniques in this research include in-depth interviews with informants using an interview guide as a data collection tool. The results show long-distance communication is conducted by children and parents through social media, especially WhatsApp, with frequent communication. The children and parents interact almost daily. Communication barriers that arise include semantic barriers or double interpretation of communication messages. Relationship maintenance efforts apply elements of positivity, openness, assurance, joint activities, mediated communication, and avoidance. Self-disclosure between children and parents involves applying a privacy boundary between private information and collective information. Communication management regarding privacy issues is handled through privacy secrecy commitments and threat methods between children and parents. Tensions in the parent-child relationship arise due to privacy turbulence, particularly due to intentional or unintentional privacy breaches and misunderstandings about privacy commitments. Children and parents manage conflicts in their longdistance relationships by evaluating and improving communication and strengthening commitments